(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
The article is an oral transcription from the closing keynote panel entitled Decolonizing the Curriculum? Transformation, Emotion, and Positionality in Teaching, at the 18th Fashion International Colloquium, at the University of Fortaleza, UNIFOR, Brazil, on September 23rd, Saturday, at ten in the morning. The panel was composed of the designers-researchers Douglas Santos and Letícia Vieira, who graduated from the Federal University of Ceará (UFC), and Professor Sarah Cheang, whose presentation text was a joint work with her colleague Professor Shehnaz Suterwalla, from the Royal College of Art, London, United Kingdon. Mi Medrado, who mediated the panel, previously translated the conference presentation.